Elucidating cooperative genetic events in DCIS progression in mutant p53 –driven breast cancer - Rhiannon L. Morrissey; Joy M. McDaniel; Gilda P. Chau; Xiaoping Su; Mitheera V; Vidhi Chandra; Beverly R. E. A. Dixon; Adel K. El-Naggar; Alastair M. Thompson; Guillermina Lozano (Proceedings of the National Academy of Sciences, 2026)
Ductal carcinoma in situ (DCIS) is a precursor mammary lesion characterized by abnormal epithelial cells in mammary ducts that remain confined to the luminal space. Not all DCIS becomes invasive, and no strategy currently exists in patients to stratify indolent DCIS from DCIS at risk of progression. Several studies of human DCIS and breast cancer suggest that TP53 mutations occur early in DCIS. However, TP53 mutation alone is insufficient for DCIS formation or transformation to invasive disease. Using an autochthonous somatic mouse model of Trp53 R245W induced breast cancer (equivalent to the TP53 R248W hotspot mutation in humans), we identified DCIS lesions. Through exome sequencing and low-pass whole-genome sequencing, we identified additional genomic changes shared between DCIS and invasive tumors. This comparison nominated seven murine candidate genes, with eight human orthologs. We assessed the cooperativity of these genes with mutant TP53 in human breast cells using acinar morphogenesis and migration assays. Overexpression of TMEM267 , which encodes a transmembrane protein overexpressed in 22% of TP53 missense mutant breast cancer cases, in cells with mutant TP53 caused a significant increase in the filled duct, DCIS-like phenotype. We nominate TMEM267 as a cooperating event with mutant TP53 in DCIS progression.